Religion and Multiculturalism at Pesantren Sunan Pandanaran and Mu'allimin Yogyakarta - Niswatin Faoziah; Hasan Mahfudh; Rima Ronika (Graduate Program of Pontianak Institute of Islamic Studies, 2016)
This paper discusses the role of pesantren (Islamic boarding school) education in developing multicultural values at Sunan Pandanaran and Muallimin Pesantren Yogyakarta. Through field studies, the findings of this research are: First, the multicultural values are reflected and have become good principles at Sunan Pandanaran or Muallimin Pesantren Yogyakarta despite the difference in characteristics. Second, pesantren education –both at Sunan Pandanaran and Muallimin Pesantren Yogyakarta– have an important contribution to the development of multicultural values each with different traits and characteristics. Third, some teachers with little understanding of multiculturalism have become a major obstacle in pesantren education especially with regard to the multicultural values. Moreover, in the context of multicultural education curriculum development, the dilemma of self-identity also becomes another problem.